Evaluation the sedative and analgesic effects of tramadol and chlorpromazine alone or as a combination in chicks - Manahel Allawi Abdulla Aljbori; Rawnaq Faris Abdulqader Alshalchi; Ghada Abdulmunem Faris (Kufa Journal for Veterinary Medical Sciences, 2021)
The goal of this study was to assess the pain-relieving action of tramadol alone or when administered with chlorpromazine and screening for analgesic effects by using sedative non-analgesic doses of tramadol and chlorpromazine when injected together in chicks. the analgesic ED50 of tramadol was 0.8 mg/kg body weight ( intra muscular injection), and the sedative ED50 of chlorpromazine was 8.6 mg / kg of body weight (intraperitoneal injection). Based on Isopolographic analysis, the type of drug interaction between tramadol and chlorpromazine was determined when injected together in a ratio by 1: 1, 1: 0.5 and 0.5: 0.5 from the median effective dose(ED50 )of tramadol and the median effective dose of chlorpromazine was synergetic interaction. Thus conclude that combination of tramadol and chlorpromazine with sedative non-analgesic doses is ideal for a good analgesic effect of pain in chicks